Fatigue life estimation of bio-composite materials - Mat Jusoh, Suriani; Ali, Aidy; Abdan, Khalina; Salit, Mohd Sapuan; Haftirman (2015)
In this study, fatigue life of bio-composite materials was predicted due to manufacturing defects fatigue damage modes. Kenaf bast fibres were used to fabricate a bio-composite material with epoxy as a binding material. The bio-composites were manufactured using a hand lay-up process. The defects in the Kenaf/epoxy bio-composite were determined by a non-destructive technique using Infrared (IR) thermal imager. The thermography analyses were verified by optical microscope and scanning electron microscope (SEM) investigations. Determinations of fatigue damage has been predicted and it found that it damage has been fixed with the predicting results. Then, the Mathematical model for estimating fatigue life by IR thermal imaging technique based on damage accumulation model is proposed. This proposed model is named as S-IR thermal imaging fatigue life model.